Woolf’s crotchets: textual cryogenics in To The Lighthouse - McLoughlin, K (Taylor & Francis, 2014)
Virginia Woolf’s To The Lighthouse (1927) is – as is well known – punctuated by a number of angular vertical marks. Within these marks, which are the square brackets known as crotchets (as opposed to the round brackets known as lunulae), certain events take place. A man, reading Virgil, blows out a candle. Another man misses his wife who has just died. A young woman gets married. She dies after childbirth. Young men are killed by a shell in a war. The first man publishes a successful collection of war poetry. Another woman has her bag carried up to a house. A boy cuts a square from a fish to bait his rod. The woman whose bag was carried up contemplates the sea. This article considers what might connect these passages, already distorted in the paraphrasing. Does the fact that they are, uniquely in the novel, enclosed in crotchets indeed require them to be read as connected? The article proposes a re-orientation of critical readings of Woolf’s crotchets from a horizontal, hierarchical, elegiac axis informed by the aesthetics of Post-Impressionism to a vertical axis of eulogy and (life-)preservation sited in the context of the First World War.